The Conceptual Model for Estimation and Opmimization of the Regional Informatization Process Development - E. S. Kadtsyna (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
The research aims at the development of theoretical and methodological provisions connected with developing the regional informatization process. There is a need in identifying the approach to designing and supporting information policy dealing with informatiztion development on the regional level. The article puts forward a conceptual model, which grounds the necessity of the complex approach to estimation and optimization of the process of regional informatization development. The model implies systematization and amendment of the existing theoretical and methodological provisions and approaches connected with estimation and optimization of development. With the help of methodological tools proposed within the frames of the model the complex and diversified approach to the problem of regional informatization can be possible. It includes the key components of information policy: identifying the level of information and technological potential of the regional economy development, obtaining the adequate estimation of efficiency of the current development of information and technological processes in different sectors and hierarchical levels of the regional economic system with subsequent development and substantiation of mechanisms of optimizing the information process development. Within the frames of the model the author grounds the need to extend methodological basis connected with the development of practical mechanism of optimizing the process of regional informatization development as one of the most important tools of information policy. The findings of the research can be used in the process of designing and correcting regional strategic programs of informatization development and as a material for further theoretical and applied research in the field of developing information and technological processes of regional economic systems.